The Effect of Pollen Type on Some Fruit Traits and Production Quantity of Date Palm Trees Phoenix Dactylifera L. For Agricultural Cultivar Al-Ibrahimi - Uday Hatem Khaeer Abed1 , Abed-Almajeed Abed-Alazeez2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study was conducted during the agricultural season 2019 in one of the orchards of the district of Heat,Al-Hassania (Shamiya) Village in Al-Anbar Governorate, know the effect of different pollen male grainstype (Ghanami Ahmar, Ghanamy akhdar, samesmi , Khikri adi ) on some fruits traits and the amount ofproduction the date palm of the agricultural cultivar AL-Ibrahimi, The results indicated that the best pollenused to pollinate the agricultural cultivar Ibrahimi it is for grains of the vaccine Khikri adi, characterizedby giving the best qualitative qualities of fruits Average weight fruits and diameter in the Khalal stageand average diameter and weight stromal layer in the stage dates (11.59 g , 2.36 cm , 1.77 cm , 9.96 g)respectively , the Ghanami Ahmar vaccine was distinguished by giving the best quantitative fruit qualitiesthe average of percentage for fruits contract and raceme weight (86.60 % , 16.87 Kg ) respectivel .